Progress in the pharmacological treatment of human cystic and alveolar echinococcosis: Compounds and therapeutic targets. - Mar Siles-Lucas; Adriano Casulli; Roberto Cirilli; David Carmena (Public Library of Science (PLoS), 2018)
Human cystic and alveolar echinococcosis are helmintic zoonotic diseases caused by infections with the larval stages of the cestode parasites Echinococcus granulosus and E. multilocularis, respectively. Both diseases are progressive and chronic, and often fatal if left unattended for E. multilocularis. As a treatment approach, chemotherapy against these orphan and neglected diseases has been available for more than 40 years. However, drug options were limited to the benzimidazoles albendazole and mebendazole, the only chemical compounds currently licensed for treatment in humans. To compensate this therapeutic shortfall, new treatment alternatives are urgently needed, including the identification, development, and assessment of novel compound classes and drug targets. Here is presented a thorough overview of the range of compounds that have been tested against E. granulosus and E. multilocularis in recent years, including in vitro and in vivo data on their mode of action, dosage, administration regimen, therapeutic outcomes, and associated clinical symptoms. Drugs covered included albendazole, mebendazole, and other members of the benzimidazole family and their derivatives, including improved formulations and combined therapies with other biocidal agents. Chemically synthetized molecules previously known to be effective against other infectious and non-infectious conditions such as anti-virals, antibiotics, anti-parasites, anti-mycotics, and anti-neoplastics are addressed. In view of their increasing relevance, natural occurring compounds derived from plant and fungal extracts are also discussed. Special attention has been paid to the recent application of genomic science on drug discovery and clinical medicine, particularly through the identification of small inhibitor molecules tackling key metabolic enzymes or signalling pathways.